EDUKASI ROBOTIKA SISWA SDN KECAMATAN GAYUNGAN SURABAYA DAN PENGEMBANGAN SOFTSKILLNYA - Woro Setyarsih (Universitas Negeri Surabaya, 2020)
Educational technology of robotics has been done to students of two public elementary schools in GayunganDistrict, Surabaya through community service (PpM) scheme of Science and Technology for Society (IbM).This activity aims to introduce the early development of technology of the present and future to the studentsand for the soft skill development of students who are poorly embedded in curricular and co-curricularactivities. This training activity begins with the introduction of the general theory of robotics and electricalcomponents used, installing electrical components on PCBs and soldering them, assembling drivercomponents, installing robotic bodies, and assembling remote control robot drives, and testing the feasibilityof their robot performance. The training is held in 5 meetings and ends with robot tournaments of the students'work. Learning outcomes in the form of knowledge about robotics, learning experiences, learning products(student work in the form of robots), and soft skill development have been obtained by the partner students.The results show that through the education of robotics, soft skill development in students can be done well.